Vascular Plants of the Coastal Midnapore District, West Bengal - Ananda Rao, T.; Mukherjee, A. K.; Banerjee, L. K. (Indian Forester, 1970)
An ecologically annotated inventory of the species growing in different habitats in the coastal belt of Midnapore District, West Bengal is presented. This list includes 156 species belonging to 120 genera and 55 families. It has a few members which are not reported from the gangelic Sundriban area or Orissa coast and includes a large number of local plants chiefty represented by agrestals/ruderals.